Kreativitas dan Inovasi Terhadap Peningkatan Volume Penjualan di Masa Pandemi - Faruk; Dzurrotun Nafis (Idarotuna : Journal of Administrative Science, 2023)
The impact of the crisis due to the pandemic can be felt by all industrial sectors, including the franchise industry, where business actors are required to be able to adapt, innovate and collaborate in order to develop and survive during a pandemic. This study aims to determine the effect of creativity and innovation on increasing sales volume at CV. Surabaya Entrepreneurial Spirit during a pandemic. The research method used is a quantitative method with data collection techniques using observation and questionnaires that have a relationship with the subject matter. The sampling technique used was purposive sampling in order to obtain 34 respondents as a sample. The following methods of data analysis were used: T and F tests with a significance level of 5% using the SPSS 25 program, Data Validity Test, Reliability Test, Multiple Linear Regression Analysis, and Classical Assumptions Analysis. The use of secondary data gathering methods, such as observation and documentation, along with a literature evaluation can strengthen the primary data used in this study. The findings demonstrated that during a pandemic, CV. Entrepreneurial Spirit saw an increase in sales volume that was both positive and significant as a result of both creativity and innovation. The significant number that results from the value of fcount > ftable, or 3.464 > 3.304, is 0.044 0.05. Innovation and creativity are two interrelated parts that cannot be separated. Many businesses around the world have found success because of their inventiveness in developing new products, including both goods and services. Because without innovation to make it happen so that it becomes something new, ideas or creativity alone are insufficient. Conversely, creativity without innovation will not be able to compete in the current sectors.